S117 Survival In Patients With Malignant Pleural Effusions Who Developed Pleural Infection: A Retrospective Case Review From 6 Uk Centres. (10th November 2014) - Bibby, AC; Slade, GC; Morley, AJ; Fallon, J; Psallidas, I; Clive, AO; Pepperall, J; Slade, MG; Stanton, AE; Rahman, NM; Maskell, NA
Abstract : Background: The incidence of malignant pleural effusions (MPE) is increasing and overall prognosis remains poor. In-dwelling pleural catheters (IPCs) relieve symptoms, but increase the risk of pleural infection. We reviewed survival times of cases of pleural infection in patients with IPCs for MPE from 6 UK centres. Methods: Baseline data were collected for all IPC insertions from 1/1/05 to 31/1/14. Survival times were analysed by underlying tumour. Results were compared with national data, and with data from a cohort of 789 patients with MPE (the LENT cohort). LENT scores were used to calculate individual predicted life expectancy, which was compared with actual survival. Results: Of 672 IPCs inserted across 6 centres during the study period, 25 patients (3.6%) experienced pleural infection. 19/25 were male, median age 69 (range 35–79). 12/25 had mesothelioma, 8/25 lung cancer, 3/25 breast cancer, 1/25 lymphoma and 1/25 thyroid cancer. 18/25 had a performance status of 0–1, and 19/25 received oncological treatment. Survival with MPE and pleural infection compared favourably with the LENT cohort (see figure 1 ). Median survival with mesothelioma and pleural infection was 753 days (95% confidence interval 446–1089) compared with 339 days in the LENT cohort (95% CI 267–442) and less than 365 days in nationally reported data. Patients with lung cancer and pleural infection also outlived their LENT counterparts; median survival of 138 days (95% CI 62–479) versus 74 days (95% CI 60–90). Patients with breast cancer had similar survival times (167 vs 192 days). LENT scores were calculated where possible. 9/13 (69%) outlived their predicted life expectancy. 16/25 (64%) developed infection within 90 days of IPC insertion. There was no difference in survival times between patients with early and late infection (p = 0.6). Discussion: In this series of patients with IPCs, pleural infection was associated with longer survival with mesothelioma and lung cancer, but not breast cancer. Most patients experienced early infection, suggesting this result isn't simply a result of higher infection rates in patients who survive longer with an IPC in situ . We propose that pleural infection stimulates a local immune response, which acts against tumour. Further studies are planned to investigate this hypothesis further.